Women''s Movements and Countermovements : the Quest for Gender Equality in Southeast Asia and the Middle East. - Derichs, Claudia (Cambridge Scholars Publishing, 2014)
The relationship between social movements and their countermovements is an underrepresented research topic, given the bulk of social movement studies that have been published to date. Moreover, empirical research on this topic primarily covers certain geographic areas of the world, specifically what is commonly called the ""global North"". The mobilization of religious and women's movements against social change, which strive for a preservation of the status quo and can be held responsible for ...